Preclinical evaluation of the RBD-Trimeric vaccine: A novel approach to strengthening biotechnological sovereignty in developing countries against SARS-CoV-2 variants - Luis Flórez; Daniel Echeverri-De la Hoz; Alfonso Calderón; Hector Serrano-Coll; Caty Martinez; Camilo Guzmán; Bertha Gastelbondo; German Arrieta; Ariel Arteta; Tania Márquez; Ricardo Rivero; Salim Máttar (Travel Medicine and Infectious Disease)
New immunogens against emerging new virus variants are essential for controlling new variants. Methods: A preclinical study in which a receptor-binding domain (RBD) trimer was designed in silico with information from the Beta (B.1.351), Omicron (BA.5), and Wuhan 1 variant. A three-dimensional model of the RBD-trimer was made, and the synthesis of the trimer was based on the RBD domain of the S protein of Beta and Omicron. For the experimental trials, 63 BALB/c mice were immunized and divided into three groups: control (n = 15), adjuvant (n = 15), and RBD-trimer (n = 33). Results: 81 % (13/16), 90 % (9/10), and 85 % (6/7) of BALB/c mice that received one dose, two doses, and three doses, respectively, seroconverted. Significant statistical differences (p < 0.001) were found between the experimental group vaccinated with the RBD-trimer, the group with adjuvant, and the control group. The booster did not show significant differences (p > 0.05. No inflammatory or cellular changes were observed, highlighting the safety of the RBD vaccine candidate. Kinetics and seroconversion of 75 % were obtained in the mice with two doses of tri-RBD. (P < 0.0001). Conclusions: Applying two doses of the RBD vaccine candidate in BALB/c mice was safe and immunogenic against SARS-CoV-2. This study provides support for the country's biotechnological sovereignty and its potential contribution to public health in Colombia.